Molybdenum supplementation may increase sulfides in the human colon - Brian James Grech (Archives of Clinical Gastroenterology - Peertechz Publications, 2022)
I have observed what seems to be a rare but novel symptom that has not been documented in the medical literature, in a subject that I have been studying. The observation was a worsening of flatus and stool odor in this subject, a few days after the subject started an unphysiologically high dose of dietary molybdenum.